Midterm Outcomes and Predictors of Clinical Success with the KineSpring Knee Implant System. Issue 6 (January 2013) - London, Nicholas J.; Smith, Jon; Miller, Larry E.; Block, Jon E.
The purpose of this study was to (1) evaluate joint pain and function in knee osteoarthritis (OA) patients treated with a joint-sparing, extracapsular implant and (2) identify patient characteristics that influenced clinical outcomes. This study included 99 patients with symptomatic medial knee OA refractory to conservative care who were treated with the KineSpring Knee Implant System and followed for a mean of 17 months (range, 1.5 to 48 months). All devices were successfully implanted and activated with no intraoperative complications. Statistically significant mean improvements of 56%, 50%, and 38% were observed for Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) Pain, Function, and Stiffness scales, respectively (all P < 0.001). Regardless of gender, age group, body mass index classification, or disease severity, all WOMAC domain scores significantly improved during the postoperative follow-up period. WOMAC clinical success rates were 77.8% for Pain, 77.8% for Function, and 68.7% for Stiffness. Neither gender, age group, body mass index classification, nor disease severity predicted clinical success in any WOMAC domain. In conclusion, the KineSpring System yields clinically meaningful improvements in joint pain and function in patients with medial knee OA. Additionally, unlike joint-altering procedures such as knee arthroplasty or high tibial osteotomy, patient characteristics had little association with postoperative clinical outcomes.